2007
DOI: 10.1086/510710
|View full text |Cite
|
Sign up to set email alerts
|

Alfven Waves and Turbulence in the Solar Atmosphere and Solar Wind

Abstract: We solve the problem of propagation and dissipation of Alfvenic turbulence in a model solar atmosphere consisting of a static photosphere and chromosphere, transition region, and open corona and solar wind, using a phenomenological model for the turbulent dissipation based on wave reflection. We show that most of the dissipation for a given wave-frequency spectrum occurs in the lower corona, and the overall rms amplitude of the fluctuations evolves in a way consistent with observations. The frequency spectrum,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
230
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(237 citation statements)
references
References 44 publications
7
230
0
Order By: Relevance
“…The amount of power in parallel propagating waves at 1 AU is a matter of debate [16]. Some models suggest counterpropagating waves are much more intense in the subAlfvénic corona, below 10 − 15 solar radii [35]. Our observations, however, show a very sharp dependence on δv c αp as calculated with the local value of C A .…”
Section: Figmentioning
confidence: 61%
“…The amount of power in parallel propagating waves at 1 AU is a matter of debate [16]. Some models suggest counterpropagating waves are much more intense in the subAlfvénic corona, below 10 − 15 solar radii [35]. Our observations, however, show a very sharp dependence on δv c αp as calculated with the local value of C A .…”
Section: Figmentioning
confidence: 61%
“…For example, the production of reliable chromospheric magnetograms may replace, or at least complement, the current use of photospheric magnetograms. Additionally, the incorporation of self-consistent treatments for the heating of the corona and acceleration of the solar wind (Cranmer, 2010;Rappazzo et al, 2007;Buchlin and Velli, 2007;Verdini and Velli, 2007) should provide more accurate global solutions, as well as a basic test for the physics underlying these ideas. Finally, from an observational perspective, studies of STEREO remote-sensing observations and in-situ measurements are continuing to reveal new insights into the global properties of the inner heliosphere (e.g., Riley et al, 2010a).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Note here that a different approach in literature is based on a use of the Elsässer variables (Velli 1993;Hollweg & Isenberg 2007;Verdini & Velli 2007;Verdini et al 2009). For instance, Velli (1993) used a Fourier approach, demonstrating that wave reflection is a global phenomenon.…”
Section: Physical Model Considered In This Papermentioning
confidence: 99%
“…It has been shown that Alfvén waves may become nonlinear already in the chromosphere, exerting a ponderomotive force on magnetoacoustic waves (Suzuki & Inutsuka 2005;Verdini & Velli 2007;Verdini et al 2009;Matsumoto & Shibata 2010). Numerical simulations of Alfvén waves launched from the chromosphere reveal that high-frequency modes are attenuated before they reach the corona by coupling with magnetoacoustic waves (Matsumoto & Shibata 2010).…”
Section: Introductionmentioning
confidence: 99%